Combination With Tomatidine Improves the Potency of Posaconazole Against Trypanosoma cruzi - Rocha-Hasler, Marianne; de Oliveira, Gabriel Melo; da Gama, Aline Nefertiti; Fiuza, Ludmila Ferreira de Almeida; Fesser, Anna Frieda; Cal, Monica; Rocchetti, Romina; Peres, Raiza Brandão; Guan, Xue Li; Kaiser, Marcel; Soeiro, Maria de Nazaré Correia; Mäser, Pascal (Frontiers in Cellular and Infection Microbiology, 2021)
Azoles such as posaconazole (Posa) are highly potent against Trypanosoma cruzi. However, when tested in chronic Chagas disease patients, a high rate of relapse after Posa treatment was observed. It appears that inhibition of T. cruzi cytochrome CYP51, the target of azoles, does not deliver sterile cure in monotherapy. Looking for suitable combination partners of azoles, we have selected a set of inhibitors of sterol and sphingolipid biosynthetic enzymes. A small-scale phenotypic screening was conducted in vitro against the proliferative forms of T. cruzi, extracellular epimastigotes and intracellular amastigotes. Against the intracellular, clinically relevant forms, four out of 15 tested compounds presented higher or equal activity as benznidazole (Bz), with EC50 values ≤2.2 μM. Ro48-8071, an inhibitor of lanosterol synthase (ERG7), and the steroidal alkaloid tomatidine (TH), an inhibitor of C-24 sterol methyltransferase (ERG6), exhibited the highest potency and selectivity indices (SI = 12 and 115, respectively). Both were directed to combinatory assays using fixed-ratio protocols with Posa, Bz, and fexinidazole. The combination of TH with Posa displayed a synergistic profile against amastigotes, with a mean ΣFICI value of 0.2. In vivo assays using an acute mouse model of T. cruzi infection demonstrated lack of antiparasitic activity of TH alone in doses ranging from 0.5 to 5 mg/kg. As observed in vitro, the best combo proportion in vivo was the ratio 3 TH:1 Posa. The combination of Posa at 1.25 mpk plus TH at 3.75 mpk displayed suppression of peak parasitemia of 80% and a survival rate of 60% in the acute infection model, as compared to 20% survival for Posa at 1.25 mpk alone and 40% for Posa at 10 mpk alone. These initial results indicate a potential for the combination of posaconazole with tomatidine against T. cruzi.